2020
DOI: 10.12681/mms.22496
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological and behavioural responses to salinity and temperature stress in cyclopoid copepod Oithona davisae with comments on gender differences

Abstract: The gender differences in reaction to salinity (3-50) and temperature (6-26°C) stress were studied in the thermophilic cyclopoid copepod Oithona davisae, introduced in the brackish temperate Black Sea since 2001. Both females and males possessed similar salinity tolerance ranges (6–40) irrespective of the salinity change rate, and females displayed a striking osmotic control upon sharp (18-40 and 40-18) salinity shocks. By contrast, the temperature response of males and females were different. Torpidity was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…At even much higher values (up to 80 ind. ml −1 ), the cyclopoid Oithona davisae showed metabolic rates in proportion to the temperature although the motor activity parameters were unaffected by short-term crowding [64,65]. The density levels adopted in the present experiments could consequently be used in observational and behavioural studies or in rearing conditions without expected consequences on animal health or motion patterns.…”
Section: Discussionmentioning
confidence: 99%
“…At even much higher values (up to 80 ind. ml −1 ), the cyclopoid Oithona davisae showed metabolic rates in proportion to the temperature although the motor activity parameters were unaffected by short-term crowding [64,65]. The density levels adopted in the present experiments could consequently be used in observational and behavioural studies or in rearing conditions without expected consequences on animal health or motion patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Swarms of D. oculata have also been reported from areas with high salinity fluctuations (Kurt, 2018; Thompson, 1991). Another cyclopoid copepod often reported from a similar habitat Oithona davisae could withstand a wider range of salinity from 6 to 40 ppt (Svetlichny et al, 2021). The adaptation of copepods to highly fluctuating salinity conditions is facilitated through osmoregulation (Bayly & Boxshall, 2009; Svetlichny & Hubareva, 2014) by regulating the concentration of intracellular free amino acids in their body (Burton & Feldman, 1982; Goolish & Burton, 1989) and the capacity to survive at different salinity levels is mostly species specific.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not find an association between salinity and O. davisae abundance. However, physiological experiments have shown that O. davisae is highly adapted to tolerate a wide salinity range (3-40) (Svetlichny & Hubareva, 2014;Zagami et al, 2018;Svetlichny et al, 2020).…”
Section: Temporal Variability Of D Oculata and O Davisae In The Southeastern Levantine Seamentioning
confidence: 99%